Force-velocity profiling during the braking phase of countermovement jump: Relationship to eccentric strength and validity of the 2-point method - Nishiumi, D.; Yamaguchi, S.; Kurokawa, T.; Wakamiya, K.; Hirose, N. (The Journal of Strength and Conditioning Research, 2023)
The aims of this study were threefold: to investigate the force-velocity profile during the braking phase (bFVP) of the countermovement jump (CMJ) and its relationship with other performance indicators, and whether it could be measured using the two-point method. Sixteen trained men performed 6 different loaded CMJs (0%, 32 kg, 60, 80, 100, and 120% body mass), and eccentric strength measurements were determined. Scatter plots were created using the mean force and velocity during the braking phase of each loaded CMJ. The corrected Akaike`s information criterion (AICc) was calculated by fitting linear, quadratic, and cubic regression equations to the bFVP and compared using the 1-way analysis of variance and Bonferroni`s post hoc tests. A correlation analysis was performed between the bFVP and other performance indicators. A bias assessment was performed to validate the 2-point method of the bFVP. The significance level was set at p < 0.05. The AICc in the linear regression equation was significantly lower (p < 0.05) than those in the other regression equations. Significant correlations were found between the slope and theoretical maximum force of the bFVP obtained from the linear regression equation and eccentric 1 repetition maximum. The acceptable condition for bias was met by 0-120%. The bFVP is likely to have a linear relationship and can be associated with eccentric strength. Furthermore, the 2-point method in bFVP has validity.